Solving the riddle by puzzling it out: overcoming the challenges of harm–benefit analysis by assembling a compound model and practice-oriented tool - Hajosi, Dominik; Grimm, Herwig (Frontiers in Veterinary Science, 2025)
The practical application of harm–benefit analysis (HBA), a requirement mandated by European Union Directive 2010/63/EU, has been extensively examined. However, reviewing bodies can access only sparse and often incomplete HBA guidance. This study develops a composite HBA method composed of the relevant and useful elements from current guidance documents and provides instructions on conducting such an analysis. It redefines HBA approaches, eliminating redundant aspects while meeting the Directive’s requirements. This novel compound HBA method includes a clear procedural methodology to guide project applicants, reviewing bodies, and authorities in transparent and coherent decision-making.